1990
DOI: 10.1111/j.1600-0773.1990.tb00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Aminotriazole Effects on Lung and Heart H2O2 Detoxifying Enzymes and TBA‐RS at Two pO2

Abstract: In order to clarify the physiological role in vivo of H2O2-detoxifying enzymes at low and high levels of O2 tension we studied catalase (CAT), glutathione peroxidases (GP), and in vivo peroxidation (TBA-RS) in the lung and heart of Rana perezi frogs chronically treated with hyperoxia, aminotriazole (AT) -a CAT inhibitor-, or both. Hyperoxia did not change CAT, GP or TBA-RS. Aminotriazole caused an almost complete depletion of CAT, a 30% decrease of GP and a 132% (lung) to 200% (heart) increase of TBA-RS. Chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The findings of our investigation strongly corroborate the earlier reports of CAT inhibition by AMT in various animal models like fish and frog (Lopez-Torres et al 1990;Lushchak et al 2003;Bagnyukova et al 2005). In a recent study on cotton bollworm Helicoverpa armigera, Goud et al (2012) inhibited catalase by another catalase inhibitor, salicylic acid, and found that all eight isozymes observed in their study except cat1 (one of the isozymes of catalase)were inhibited by salicylic acid.…”
Section: Figuresupporting
confidence: 92%
“…The findings of our investigation strongly corroborate the earlier reports of CAT inhibition by AMT in various animal models like fish and frog (Lopez-Torres et al 1990;Lushchak et al 2003;Bagnyukova et al 2005). In a recent study on cotton bollworm Helicoverpa armigera, Goud et al (2012) inhibited catalase by another catalase inhibitor, salicylic acid, and found that all eight isozymes observed in their study except cat1 (one of the isozymes of catalase)were inhibited by salicylic acid.…”
Section: Figuresupporting
confidence: 92%
“…In addition, Lopes-Torres et al (1990) and Bagnyukova et al (2003) reported that catalase is the main H 2 O 2 -detoxyfying enzyme. The decreased CAT activity may be due to the flux of superoxide radicals, which have been shown to inhibit CAT activity (Stanic et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…The role of catalase in defense against peroxides is not fully understood. Some authors suggest that catalase is the main H 2 O 2 -detoxifying enzyme (Barja de Quiroga et al, 1988;López-Torres et al, 1990) and that it plays the major role in the decomposition of H 2 O 2 when its intracellular concentration is highly elevated (Hermes-Lima, 2005), while other studies found that GPx was more efficient at detoxifying H 2 O 2 (Remacle et al, 1992) and that low levels of H 2 O 2 are better controlled by GPx (Hermes-Lima, 2005). The catalase inhibition at pH 6.0 was probably compensated by the increase in both GPx activity and glutathione concentration.…”
Section: Discussionmentioning
confidence: 99%